Lysine at position 329 within a C-terminal dilysine motif is crucial for the ER localization of human SLC35B4. - Bożena Bazan; Maciej Wiktor; Dorota Maszczak-Seneczko; Teresa Olczak; Beata Kaczmarek; Mariusz Olczak (PLoS ONE, 2018)
SLC35B4 belongs to the solute carrier 35 (SLC35) family whose best-characterized members display a nucleotide sugar transporting activity. Using an experimental model of HepG2 cells and indirect immunofluorescent staining, we verified that SLC35B4 was localized to the endoplasmic reticulum (ER). We demonstrated that dilysine motif, especially lysine at position 329, is crucial for the ER localization of this protein in human cells and therefore one should use protein C-tagging with caution. To verify the importance of the protein in glycoconjugates synthesis, we generated SLC35B4-deficient HepG2 cell line using CRISPR-Cas9 approach. Our data showed that knock-out of the SLC35B4 gene does not affect major UDP-Xyl- and UDP-GlcNAc-dependent glycosylation pathways.